2010
DOI: 10.1002/star.201000023
|View full text |Cite
|
Sign up to set email alerts
|

Starch characterization of different blue maize varieties

Abstract: Maize shows a significant genetic diversity, giving origin to a great number of varieties, hybrids, and genotypes. Recently, the pigmented corn varieties have received increased interest because of their anthocyanin contents. Although starch is the major component of the pigmented corn, only a few studies have been conducted on this constituent. The aim of this work was to evaluate the physicochemical properties and structural characteristics of starch isolated from six blue maize varieties grown in Mexico. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…The gelatinization enthalpy (Δ H G ) values ranged from 7.7 to 11.3 J/g (Chapalote and Blando de Sonora, respectively) and were similar to those observed by Li et al (1994) (8.2–13 J/g) in 35 tropical maize genotypes. The blue landrace Elotero de Sinaloa had a gelatinization enthalpy of 11.2 J/g, which falls within the range of values reported by De la Rosa‐Millán et al (2010) for six blue maize accessions of Mexico (9.6–12.2 J/g). Cooke and Gidley (1992) reported that gelatinization enthalpy is an indicator of starch crystallinity (double helices of amylopectin chains), and other authors reported that low amylopectin starches showed a low gelatinization enthalpy, which was associated with a lower degree of crystallinity (Gernat et al 1993; Matveev et al 2001).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The gelatinization enthalpy (Δ H G ) values ranged from 7.7 to 11.3 J/g (Chapalote and Blando de Sonora, respectively) and were similar to those observed by Li et al (1994) (8.2–13 J/g) in 35 tropical maize genotypes. The blue landrace Elotero de Sinaloa had a gelatinization enthalpy of 11.2 J/g, which falls within the range of values reported by De la Rosa‐Millán et al (2010) for six blue maize accessions of Mexico (9.6–12.2 J/g). Cooke and Gidley (1992) reported that gelatinization enthalpy is an indicator of starch crystallinity (double helices of amylopectin chains), and other authors reported that low amylopectin starches showed a low gelatinization enthalpy, which was associated with a lower degree of crystallinity (Gernat et al 1993; Matveev et al 2001).…”
Section: Resultssupporting
confidence: 83%
“…The gelatinization and retrogradation parameters of the maize starches are shown in Table IV. The peak gelatinization temperature ( T pG ) varied from 71.9 (Reventador) to 73.0°C (Blando de Sonora); these results are within the range reported by De la Rosa‐Millán et al (2010) (67.0–73.8°C) in different varieties of Mexican blue maize. The highest T pG of Blando de Sonora starch corresponds with its highest crystallinity (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The wet‐milling characteristics of GEM accessions (Singh et al 2001), GEM lines (Taboada‐Gaytan et al 2009), and experimental maize hybrids with exotic and nonexotic origin (Taboada‐Gaytan et al 2010a, 2010b) have also been reported. Efforts conducted to study Mexican blue maize landraces are currently focused on the evaluation of their anthocyanin content (Salinas‐Moreno et al 2012), antioxidant capacity (Del Pozo‐Insfran et al 2006), and more recently their structural, morphological, physicochemical, functional, and technological properties and starch biosynthesis enzymes (Agama‐Acevedo et al 2005, 2011; Utrilla‐Coello et al 2009; De la Rosa‐Millán et al 2010). However, little information is available regarding their wet‐milling properties.…”
mentioning
confidence: 99%